Effect of xenobiotic challenge on enzymatic activity of detoxification enzymes at different exposure periods in Aedes albopictus (skuse) (Diptera: Culicidae) - Salinah Abdul Farouk; Sarah Abdul Razak; Siti Nasuha Hamzah (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The xenobiotics including insecticides such as malathion and permethrin induce the activities of detoxification enzymes and potentially leading to the development of resistance. In this study, biochemical analysis was used to characterize the time-dependent malathion and permethrin induction profile of Glutathione S-transferase (GST), α-esterase (α-est), β-esterase (β-est), Cytochrome P450 (Cyt P450) and Acetylcholinesterase (AChE), enzymes which are known to contribute to metabolic resistance in Aedes albopictus. Time-dependent induction of early fourth instar larvae with the sub-lethal concentration (LC50) of malathion (0.099 mg/L) and permethrin (0.0023 mg/L) was done at 6, 12 and 24 hours to observe the effect on the enzymatic activity under toxicological challenges. Total protein content of larvae was most elevated when the larvae were exposed to both insecticides for 24 hours. The level of total enzyme activity and specific activity of GST, as well as Cyt P450 were found to be most elevated whereas the level of α-est and β-est total enzyme and specific activity were decreased at 24 hours of treatment with malathion. A different pattern was observed for permethrin induction whereby the total enzyme and specific activity of all enzymes except Cyt P450 were highly elevated upon 24 hours of acute exposure. The level of total enzyme activity and specific activity of almost all enzymes upon acute induction with malathion and permethrin were statistically significant (p˂0.05) when compared between the induced hours and to its susceptible strain. Conclusively, these findings indicate that the continuous and prolonged exposure to sub-lethal concentration of malathion and permethrin influenced the induction of GST, α-est, β-est, Cyt P450 as well as AChE enzymatic activities.